ANALISIS BALANCED SCORECARD PADA KOPERASI KARYAWAN KRAMA YUDHA RATU MOTOR JAKARTA - Bella Devita Puteri Wardani; Hari Susanta Nugraha; Agung Budiatmo (Universitas Diponegoro, 2012)
Cooperative is an organization that puts the interests and welfare of more members in the central position of the overall cooperative activity. In the application of balanced scorecard on the use of cooperatives, there is an adjustment in the four balanced scorecard perspectives are: financial perspective, membership perspective, partnership perspective, and learning and growth perspective. The purpose of this research was to determine the performance of Cooperative of Krama Yudha Ratu Motor Employees seen from the balanced scorecard method. The achievement of the objectives of this research is to use the method of Focus Group Discussion with the employee to determine the score obtained. From the results of measurements that have been done show that the whole performance of Cooperative of Krama Yudha Ratu Motor Employees is pretty good, it is shown from the score generated from each perspective. The conclusion to be drawn from the analysis that has been done is that the balanced scorecard can be used as a method of performance measurement in the cooperative, as the balanced scorecard raised the important aspects that are ignored by the traditional performance measurement, so that the measurement results with the balanced scorecard is more comprehensive. Suggestion which can be submitted from the author is pay more attention to non-financial aspects in order to maximize the potential of cooperative and cooperative can also achieve the welfare of its members.